The Effect Of Bomo Games Training On The Gross Motor Skills Of Slightly Impaired Children In Stake Special Schools in Karawang District - Lisna Wijayanti; Dany Aulia; Habibi Hadi Wijaya; Deden Akbar Izzuddi; Muhammad Arief Setiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The Bomo Games game is inspired by Bocce Ball Games, which aims to train the gross motor skills of mentally retarded children. These children experience obstacles in terms of motor focus due to their intellectual challenges. Even though their fine motor skills are trained every day at school, gross motor exercises are only done once a week. Therefore, they are involved in games such as Bomo Games which combine moves from the game of bocce. This study aims to evaluate the effect of Bomo Games training on improving motor skills in mildly mentally retarded children. The research design used a pre-experimental method (one group pre-test post-test) by providing treatment to all samples selected using purposive sampling. The research population consisted of two groups, namely SLB Negeri 1 West Karawang and SLB Negeri Karawang Regency.